Skull metastasis from thyroid follicular carcinoma with difficult diagnosis of the primary lesion - Case report - Akdemir, I; Erol, FS; Akpolat, N; Ozveren, MF; Akfirat, M; Yahsi, S (Japan Neurosurgical Soc, 2005)
A 57-year-old male patient presented with an immobile ellipsoid mass of 6-cm diameter in the right occipitoparietal region. Cranial computed tomography showed the mass with dense contrast enhancement causing bone destruction. After embolization of the mass, total resection was performed. Histological examination showed the mass had a capsule, with no invasion of the dura mater or dermis, and the follicles of various sizes covered with mono-lined thyrocytes were full of colloid. Immunohistochemical examination showed positive staining for thyroglobulin. Postoperatively, levels of thyroid hormones were normal, and thyroid ultrasonography and technetium-99m scintigraphy showed no abnormalities. Fine needle aspiration biopsy performed at various locations of the thyroid gland revealed no atypical thyroid cells. Whole body technetium-99m scintigraphy found no abnormal bone involvement. The histological evidence was suggestive of follicular carcinoma metastasis. Surgical treatment was planned for the thyroid gland, but the patient did not consent. Two years later, the patient presented with the pain and sensitivity in the sacrum, the right iliac wing, and the right caput femoris. Computed tomography revealed lytic lesions in these areas. Bone metastases were identified. Whole body scintigraphy showed increased activity in these regions, but the cranium and all other tissues were normal. The patient underwent total thyroidectomy under a diagnosis of follicular carcinoma. The present case of a lytic skull lesion associated with normal thyroid tissue on admission but finally treated as follicular thyroid cancer emphasizes the difficulty in histological discrimination of follicular carcinoma from normal thyroid tissue.
Keywords: cranium; follicular carcinoma; metastasis